2001
DOI: 10.1152/ajpendo.2001.280.5.e770
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of insulin on peripheral and visceral tissue protein synthesis in neonatal pigs

Abstract: We recently demonstrated in neonatal pigs that, with amino acids and glucose maintained at fasting levels, the stimulation of protein synthesis in longissimus dorsi muscle with feeding can be reproduced by a physiological rise in insulin alone. In the current report, we determine whether the response of protein synthesis to insulin in the neonatal pig is 1) present in muscles of different fiber types, 2) proportional in myofibrillar and sarcoplasmic proteins, 3) associated with increased translational efficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
106
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(121 citation statements)
references
References 57 publications
13
106
2
Order By: Relevance
“…The PTP1B association with IR in muscle, but not liver, was lower in 7-compared with 26-day-old pigs (* P Ͻ 0.05). high insulin sensitivity of protein synthesis in skeletal muscle of 7-compared with 26-day-old pigs (14,37,46). Importantly, no developmental change in PTP1B activation in liver was detected, which is consistent with the previously reported lack of developmental change in insulin sensitivity in the liver (14,37).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The PTP1B association with IR in muscle, but not liver, was lower in 7-compared with 26-day-old pigs (* P Ͻ 0.05). high insulin sensitivity of protein synthesis in skeletal muscle of 7-compared with 26-day-old pigs (14,37,46). Importantly, no developmental change in PTP1B activation in liver was detected, which is consistent with the previously reported lack of developmental change in insulin sensitivity in the liver (14,37).…”
Section: Discussionsupporting
confidence: 91%
“…high insulin sensitivity of protein synthesis in skeletal muscle of 7-compared with 26-day-old pigs (14,37,46). Importantly, no developmental change in PTP1B activation in liver was detected, which is consistent with the previously reported lack of developmental change in insulin sensitivity in the liver (14,37). There were no differences in PTP1B activity between fasted and fed pigs in the current study, although studies in intact cells have shown that insulin increases PTP1B activity (25,35).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Furthermore, there seems to be a compartmentalization where proteins for export are synthesized on the rough endoplasmic reticulum while constitutive proteins are synthesized on polysomes within the cell cytosol (Connell et al, 1997). However, insulin was not involved in the stimulation of protein synthesis in the liver of neonatal pigs (Davis et al, 2001). Furthermore, no difference in albumin synthesis was found in humans with increased plasma insulin (Ballmer et al, 1995) compared with controls.…”
Section: I/g Ratiomentioning
confidence: 99%
“…Previously, our group has developed and successfully implemented a stable isotope method to measure the in vivo fractional synthesis and breakdown rates (FSR 2 and FBR, respectively) of skin protein (1)(2)(3). Using this and other methods, we and others have reported the unique features of skin and wound protein metabolism (1,2,4) and its responses to nutritional and hormonal interventions (3,5,6). Amino acid (AA) supplementations and insulin (INS) are of particular interest among these interventional factors due to their well known anabolic effect on muscle and importance in wound healing (7,8).…”
mentioning
confidence: 99%